Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2022)
This chapter is dedicated to the synthesis of O- and S-6-membered heterocycles, covering the literature published during 2019. Highlights include the most interesting chemistry dedicated of these heterocyclic ring systems, from our personal point of view, with special emphasis to the synthesis of natural oxygen derivatives. Reviews on the isolation, biological properties, biosynthesis, and total synthesis of benzannulated spiroketal natural products (19OBC8272) and of diterpene pyran- 2-ones (19OBC8943), on the natural occurrence, pharmacological properties, and structureeactivity relationships of quassinoids, a kind of triterpenoid bearing a tetrahydropyran bridge (19CPB654), on the biosynthesis of Monascus azaphilone pigment congeners containing chromene frameworks (19NPR561), and on naturally occurring 3-aryl-4H-chromen-4-ones isolated after 2012 (19NPR1156), have appeared.